Transient transcriptional events in human skeletal muscle at the outset of concentric resistance exercise training - Murton, Andrew J.; Billeter, R.; Stephens, Francis B.; Des Etages, S.G.; Graber, F.; Hill, R.J.; Marimuthu, Kanagaraj; Greenhaff, Paul L. (American Physiological Society, 2014)
We sought to ascertain the time course of transcriptional events that occur in human skeletal muscle at the outset of resistance exercise (RE) training in RE naive individuals and determine whether the magnitude of response was associated with exercise-induced muscle damage. Sixteen RE naive men were recruited; eight underwent two sessions of 5 × 30 maximum isokinetic knee extensions (180°/s) separated by 48 h. Muscle biopsies of the vastus lateralis, obtained from different sites, were taken at baseline and 24 h after each exercise bout. Eight individuals acted as nonexercise controls with biopsies obtained at the same time intervals. Transcriptional changes were assessed by microarray and protein levels of heat shock protein (HSP) 27 and αB-crystallin in muscle cross sections by immunohistochemistry as a proxy measure of muscle damage. In control subjects, no probe sets were significantly altered (false discovery rate < 0.05), and HSP27 and αB-crystallin protein remained unchanged throughout the study. In exercised subjects, significant intersubject variability following the initial RE bout was observed in the muscle transcriptome, with greatest changes occurring in subjects with elevated HSP27 and αB-crystallin protein. Following the second bout, the transcriptome response was more consistent, revealing a cohort of probe sets associated with immune activation, the suppression of oxidative metabolism, and ubiquitination, as differentially regulated. The results reveal that the initial transcriptional response to RE is variable in RE naive volunteers, potentially associated with muscle damage and unlikely to reflect longer term adaptations to RE training. These results highlight the importance of considering multiple time points when determining the transcriptional response to RE and associated physiological adaptation.